GESTÃO DE SEGURANÇA, MEIO AMBIENTE E SAÚDE:PROPOSTA DE ESTRUTURA DE SISTEMA E METODOLOGIA DE AVALIAÇÃO DE DESEMPENHO - Bobsin, Marco Aurélio (2005)
The globalization makes the business world even more complex and companies, under pressure due to issues concerning Health, Safety and Environment, are now considering the HSE issues strategic for business, actually a question of survival. This project was based on bibliographic and exploratory research on the best international and national practices of HSE management, and it presents a proposal for a Health, Safety and Environmental Management, with a methodology of evaluation of performance, in order to pursue excellence in HSE, establishing system integrating Health, Safety and Environmental, as well as providing oil an petrochemical companies, which have a certified HSE management system or system based on Plan-Do-Check-Act (PDCA), with the possibility of self-evaluation in a process of continuous improvement.